A physical activity, nutrition and oral health intervention in nursery settings: process evaluation of the NAP SACC UK feasibility cluster RCT - Rebecca Langford; Russell Jago; James White; Laurence Moore; Angeliki Papadaki; William Hollingworth; Chris Metcalfe; Dianne Ward; Rona Campbell; Sian Wells; Ruth Kipping (BMC, 2019)
Abstract Background The nutrition and physical activity self-assessment for childcare (NAP SACC) intervention has demonstrated effectiveness in the USA. A feasibility randomised controlled trial was conducted in England to adapt the intervention to the UK context. An embedded process evaluation focused on three key questions. 1. Was it feasible and acceptable to implement the intervention as planned? 2. How did the intervention affect staff and parent mediators? 3. Were the trial design and methods acceptable? Methods Twelve nurseries in south-west England were recruited and randomised to intervention or control. The intervention comprised: NAP SACC UK Partner (Health Visitor) support to nurseries to review practice and policies against best practice, and then set goals to improve physical activity, nutrition and oral health; two staff training workshops; and a web-based parent support element. The process evaluation comprised: observations of Partner training (n = 1), Partner/manager meetings (n = 5) and staff workshops (n = 10); semi-structured interviews with Partners (n = 4), managers (n = 12), staff (n = 4) and parents (n = 20); analysis of self-assessment forms, goal setting forms and Partner logbooks; and assessment of staff and parent knowledge, motivation and self-efficacy mediators. Results Overall, NAP SACC UK was feasible to implement and acceptable to nursery staff, managers, Partners and parents. The intervention was implemented as planned in five of the six intervention nurseries. Partners and managers appreciated the opportunity to review and improve nursery practices and valued the relationship forged between them. Staff rated the training workshops highly, despite attending outside of working hours. Most goals set by nurseries were achieved. However, Partners raised concerns about Health Visitors' capacity to deliver the intervention in any subsequent roll out. Mediator scores improved in all but two areas in intervention staff and parents, with decreases or minimal changes in the control group. The web-based parent element was not well used and should be removed from any subsequent trial. The trial methods were acceptable to managers, staff, Partners and parents. Conclusions Implementing and evaluating a physical activity and nutrition intervention in nursery settings is feasible and acceptable. A full RCT of NAP SACC UK (with appropriate modifications) is warranted. Trial registration ISRCTN16287377 (10 Apr 2015).